Analisis Efektifitas Pembelajaran Daring Terhadap Hasil Belajar Mahasiswa STMIK Pesat Nabire: Pendekatan Mixed Methods - Cici Kamalia; Nadine Elsya Irawati (STMIK Pesat Nabire, 2025)
This study aims to analyze the effectiveness of online learning on student academic achievement using a mixed methods approach. Data were collected through questionnaires involving 25 students and in-depth interviews with lecturers and students from STMIK Pesat Nabire. Quantitative findings show that aspects such as interaction, learning motivation, assessment, and overall satisfaction were positively rated by most respondents (70%). However, the aspect of technological readiness and accessibility scored only 60%, indicating significant technical barriers. Qualitative findings supported these results, with major concerns related to limited learning platforms and distracting home environments. It is concluded that online learning is moderately effective but requires improvements in digital infrastructure and interactive teaching strategies. This research offers recommendations for higher education institutions to adapt teaching methods to be more responsive to current digital challenges.